Building Research Ethics Capacity in Post-Communist Countries: Experience of Two Fogarty Training Programs - Strosberg, Martin A. (J Empir Res Hum Res Ethics, 2013)
The post-Communist countries of Central and Eastern Europe and Central Asia are at various stages of development with respect to their capacity to protect human research participants. We examined the impact of two Fogarty-funded programs in this region, the Union Graduate College–Vilnius University Advanced Certificate Program and the Case Western Reserve University Master’s Degree Program, by surveying these programs’ graduates and by examining alumni activities. Alumni have served in leadership roles on research ethics committees, developed and taught new courses in research ethics, and contributed to scholarship. However, political, social, and economic challenges impede the ability of graduates to maximize their effectiveness. Additional curricular attention is needed in research methodology, policy development and implementation, and the interplay between research ethics and human rights.